Mecanismos focais dos sismos em Portugal continental - Bezzeghoud, M.; Borges, J. (Física de la Tierra, 2003)
In this work all available fault plane solutions, of the shallow depth seismic events with 1.9 _ M _ 8.0 occurred in the period 1960-2003 in continental Portugal and adjacent margin, have been collected, carefully checked and analysed. The distribution of the focal mechanisms have been analysed in detail, by means of different techniques, projections and graphic representations. In first analysis, these focal mechanisms present an accentuated variability (strike-slip, inverse and oblique); however, we have identified some important patterns in the following regions: west Portuguese margin (strike-slip), Lisbon and Vale do Tejo (dip-slip), region of Évora and vicinity (strike-slip), region of Algarve (strike-slip) and inter-plates boundary zone (reverse). The geographical distribution of the horizontal projection of the axes P and T show that the orientation of the axes P is NW – SE to NNW – SSE from horizontal to sub-horizontal inclination while the axes T presents an inclination that varies from sub-horizontal, in the continental part, to subvertical, in the south margin of Algarve. It is verified that in the continent and West Atlantic margin predominate strike-slip and oblique mechanisms, while in the south margin predominate strike-slip mechanisms and inverse mechanisms. We can, however, affirm that the whole area meets under the influence of compression in an average direction NW - SE and extension in an average direction NE - SW.